1977
DOI: 10.1002/lary.5540870506
|View full text |Cite
|
Sign up to set email alerts
|

Noxious effects upon cochlear metabolism

Abstract: The influence of various toxic substances and of drugs with ototoxic side effects upon energy generation, energy utilization, and membrane processes of the cochlea were studied. None of the drugs tested interfered with energy generation to as great an extent as did anoxia or cyanide and 2,4‐dinitrophenol. Ouabain produced a pronounced interference with energy utilization of the stria vascularis. The “loop” diuretics ethacrynic acid and furosemide produced a reduction of energy utilization of a lesser degree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Patterson & Gulick, 1963), it is unlikely that suppression of cochlear respiratory enzyme activity is the primary mechanism whereby ethacrynic acid (and by implication, furosemide) exerts ototoxic effects. Similar conclusions were drawn, by Thalmann, Thalmann, Ise & Paloheimo (1977) and Kusakari, Ise, Comegys, Thalmann & Thalmann (1978), from data with furosemide.…”
Section: Discussionsupporting
confidence: 72%
“…Patterson & Gulick, 1963), it is unlikely that suppression of cochlear respiratory enzyme activity is the primary mechanism whereby ethacrynic acid (and by implication, furosemide) exerts ototoxic effects. Similar conclusions were drawn, by Thalmann, Thalmann, Ise & Paloheimo (1977) and Kusakari, Ise, Comegys, Thalmann & Thalmann (1978), from data with furosemide.…”
Section: Discussionsupporting
confidence: 72%
“…Previously, the effects of acute energy failure on the cochlea have been studied using anoxia or chemical asphyxiants such as carbon monoxide, cyanide and nitric oxide [Brown et al, 1983;Kong et al, 1996;Nuttall and Lawrence, 1979;Pai et al, 1998;Rao and Fechter, 2000;Ruan et al, 1997;Tawackoli et al, 2001;Thalmann et al, 1977]. In these studies, electrophysiological methods were primarily used to investigate the pathophysiology of cochlear dysfunction, and only a small number of morphological studies limited to the organ of Corti and spiral ganglion cells have been conducted [Kong et al, 1996;Pai et al, 1998;Ruan et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is likely to be due to an increase in an intracellular constituent to which phosphate is bound. Thalmann et al (1977) showed that phosphocreatinine levels rise when Na + -K + ATPase is inhibited by ouabain, and it is possible that a similar increase takes place in hair cells following Cisplatin.…”
Section: Discussionmentioning
confidence: 99%